Composite quartz sagger as well as preparation method and application thereof
Through the composite cassette process using fused silica and other materials, the problem of insufficient water-cooling stability and corrosion resistance of traditional cassettes is solved, and the stability and accuracy requirements of cassettes in high-temperature environments are achieved. It is suitable for new energy battery materials high performance applications.
Patent Information
- Application Number
- CN202411260001.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-10
AI Technical Summary
Traditional silhouette materials have shortcomings in water-cooling stability and corrosion resistance, which are difficult to meet the high-performance demand of battery materials in the new energy industry.
Using a composite quartz silo kettle with the first and second fused quartz as aggregate, combined with roller rod material, M70 sintered mullite, kaolin, α-alumina, cordierite and erythrite, through premix, mixing, and mortar It is manufactured in chemical, hydraulic molding and high-temperature firing processes, and has a small thermal expansion coefficient, high dimensional accuracy of finished products, good water-cool and cold shock stability, and good chemical corrosion resistance.
The silhouette used in high-temperature environment has a small thermal expansion coefficient, accurate size, stable water cooling and shock performance and good chemical corrosion resistance, and is suitable for rapid cooling and high-temperature calcining environments without alkaline environments.
Smart Images

Figure CN119118685A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of saggers, and in particular to a composite quartz sagger and a preparation method and application thereof. Background Art
[0002] With the rapid development of the new energy industry, the requirements for battery material performance are increasing. As a key component of the battery, the sagger used in the sintering process of the positive electrode material has an important influence on the performance of the material. Although traditional sagger materials such as cordierite-mullite / spinel composite materials can meet general needs, they are insufficient in water cooling stability and corrosion resistance. Therefore, it is of great significance to develop new sagger materials and their preparation methods.
[0003] Quartz ceramics are also called fused quartz ceramics, quartz glass ceramics, and quartz glass sintered products. Traditional fused quartz ceramic products are a combination of amorphous silicon dioxide made using a special production process.
[0004] Fused quartz ceramics are made of fused quartz with high purity (SiO2%>99%). Its greatest advantage is that its strength increases with the increase of temperature below 1100℃. Its strength increases from room temperature to 1100℃, and the product can still be used normally below 1300℃. Due to its advantages of low thermal conductivity, small expansion coefficient, high temperature resistance, good thermal stability and corrosion resistance, it has been widely used in metallurgy, building materials, chemical industry, national defense, scientific research and other departments; especially in the solar polysilicon industry, fused quartz is often used as a raw material to make ceramic crucibles. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a composite quartz sagger and its preparation method and application. The sagger has the characteristics of small thermal expansion coefficient, high dimensional accuracy of finished products, no deformation at high temperature, good water-cooled thermal shock stability, good chemical corrosion resistance, etc., and can be applied to various non-alkaline environments and high-temperature calcination environments with rapid temperature rise and fall.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A composite quartz sagger, wherein the thermal expansion coefficient of the sagger is ≤2.0×10 -6 / ℃, the sagger does not crack when water-cooled at a temperature of 1100℃, and the use temperature of the sagger is ≤1300℃;
[0008] The sagger uses first fused quartz and second fused quartz as aggregates; the particle size of the first fused quartz is 0.1-0.9 mm, and the particle size of the second fused quartz is 1-2 mm; the first fused quartz accounts for 18-40% of the raw materials for preparing the sagger; the second fused quartz accounts for 18-40% of the raw materials for preparing the sagger.
[0009] As a preferred embodiment of the present invention, the sagger includes the following raw materials in parts by weight: 20 to 40 parts of a first fused quartz, 20 to 40 parts of a second fused quartz, 0 to 20 parts of roller stock, 0 to 20 parts of M70 sintered mullite, 10 to 20 parts of kaolin, 0 to 20 parts of α-alumina, 0 to 40 parts of cordierite, 0 to 20 parts of andalusite, 1 to 5 parts of a binder, and 1 to 5 parts of water.
[0010] Wherein, the α-alumina is a corundum phase of more than 90%.
[0011] Cordierite is cordierite phase>90%; 200-325 mesh, 0.2-1.25mm particles, 1-2mm particles.
[0012] The roller rod material has an aluminum oxide content of more than 70%, a zirconium oxide content of 1-10%, 200-325 meshes, 0-1mm particles, and 1-2mm particles.
[0013] It should be noted that the roller rod material is an alumina roller rod, which is a roller rod that is a defective product of a kiln or is dismantled from a scrapped kiln, is obtained by crushing, and is conventionally available on the market.
[0014] As a preferred embodiment of the present invention, the sagger includes the following raw materials in parts by weight: 20 to 40 parts of a first fused quartz, 20 to 40 parts of a second fused quartz, 5 to 10 parts of M70 sintered mullite, 15 to 18 parts of kaolin, 13 to 15 parts of α-alumina, 0 to 5 parts of andalusite, 1.5 to 2 parts of a binder, and 2 to 3 parts of water.
[0015] As a preferred embodiment of the present invention, the particle size of the M70 sintered mullite is 300-350 meshes.
[0016] As a preferred embodiment of the present invention, the particle size of the andalusite is 0.1-1 mm.
[0017] As a preferred embodiment of the present invention, the binder is at least one of sodium lignin sulfonate, calcium lignin sulfonate, peach gum, yellow dextrin, white dextrin, polyvinyl alcohol, polyethylene glycol, 801 glue powder, carboxymethyl cellulose, and hydroxypropyl methyl cellulose.
[0018] The present invention also provides a method for preparing a composite quartz sagger, comprising the following steps:
[0019] (1) mixing water and a binder uniformly to obtain a mixture;
[0020] (2) uniformly mixing the first fused quartz and the second fused quartz to obtain mixed fused quartz, and uniformly mixing the mixed fused quartz and the mixture to obtain aggregate;
[0021] (3) mixing the remaining materials uniformly to obtain a base material;
[0022] (4) The aggregate and base material are mixed evenly, aged, filled into a mold, pressed, and sintered to obtain a sagger.
[0023] As a preferred embodiment of the present invention, the pressing adopts a four-column bidirectional hydraulic press, the pressing pressure is 90-120 MPa, the ejection pressure is 60-80 MPa, and the pressing time is 2-10 min.
[0024] As a preferred embodiment of the present invention, the sintering is specifically as follows: first, the temperature is increased to 450-500°C at a heating rate of 1-3°C / min, then the temperature is increased to 950-1000°C at a heating rate of 3-5°C / min, then the temperature is increased to 1320-1400°C at a heating rate of 1-3°C / min, kept warm for 3-5h, cooled to 900-950°C at a cooling rate of 1-3°C / min, then cooled to 550-600°C at a cooling rate of 3-5°C / min, and finally naturally cooled to room temperature.
[0025] The present invention also provides an application of a composite quartz sagger in preparing positive electrode materials.
[0026] The beneficial effects of the present invention are as follows: the present invention uses the first fused quartz and the second fused quartz as aggregates, controls the particle size and ratio of the two, adds roller rod material, M70 sintered mullite, kaolin, α-alumina, cordierite, and andalusite, and forms a sagger through premixing, mixing, aging, hydraulic molding, drying, and high-temperature firing. The method has a simple manufacturing process, is friendly to the working environment, does not generate any wastewater, has a low manufacturing cost, and is convenient for industrial and automated production. Because it has the characteristics of small thermal expansion coefficient, high dimensional accuracy of finished products, no deformation at high temperature, good water-cooled thermal shock stability, good chemical corrosion resistance, etc., it can be applied to various non-alkaline environments and high-temperature calcination environments with rapid temperature rise and fall. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the flow chart of water-cooled thermal shock test. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0029] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0030] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0031] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0032] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.
[0033] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0034] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.
[0035] Example 1
[0036] A composite quartz sagger comprises the following raw materials in parts by weight: 40 parts of first fused quartz, 20 parts of second fused quartz, 10 parts of M70 sintered mullite, 16 parts of kaolin, 14 parts of alpha-alumina, 2.5 parts of yellow dextrin, and 4 parts of water.
[0037] The particle size of the first fused quartz is 0.1-0.9 mm, and the particle size of the second fused quartz is 1-2 mm.
[0038] The particle size of the M70 sintered mullite is 325 meshes.
[0039] The preparation method of the composite quartz sagger comprises the following steps:
[0040] (1) mixing water and yellow dextrin uniformly to obtain a mixture;
[0041] (2) uniformly mixing the first fused quartz and the second fused quartz to obtain mixed fused quartz, and uniformly mixing the mixed fused quartz and the mixture to obtain aggregate;
[0042] (3) mixing the remaining materials uniformly to obtain a base material;
[0043] (4) The aggregate and base material are mixed evenly and aged for 24 h. The aged material is filled into a mold and pressed for 5 min using a 1500 t four-column bidirectional hydraulic press. The pressing pressure is 100 MPa and the ejection pressure is 70 MPa. The temperature is first increased to 480 °C at a heating rate of 2 °C / min, then increased to 1000 °C at a heating rate of 4 °C / min, then increased to 1380 °C at a heating rate of 2 °C / min, kept at this temperature for 4 h, cooled to 900 °C at a cooling rate of 2 °C / min, then cooled to 600 °C at a cooling rate of 4 °C / min, and finally naturally cooled to room temperature to obtain a sagger.
[0044] Example 2
[0045] A composite quartz sagger comprises the following raw materials in parts by weight: 20 parts of first fused quartz, 40 parts of second fused quartz, 10 parts of M70 sintered mullite, 16 parts of kaolin, 14 parts of alpha-alumina, 2 parts of yellow dextrin, and 2.5 parts of water.
[0046] The particle size of the first fused quartz is 0.1-0.9 mm, and the particle size of the second fused quartz is 1-2 mm.
[0047] The particle size of the M70 sintered mullite is 325 meshes.
[0048] The preparation method of the composite quartz sagger comprises the following steps:
[0049] (1) mixing water and yellow dextrin uniformly to obtain a mixture;
[0050] (2) uniformly mixing the first fused quartz and the second fused quartz to obtain mixed fused quartz, and uniformly mixing the mixed fused quartz and the mixture to obtain aggregate;
[0051] (3) mixing the remaining materials uniformly to obtain a base material;
[0052] (4) The aggregate and base material are mixed evenly and aged for 24 h. The aged material is filled into a mold and pressed for 5 min using a 1500 t four-column bidirectional hydraulic press. The pressing pressure is 100 MPa and the ejection pressure is 70 MPa. The temperature is first increased to 480 °C at a heating rate of 2 °C / min, then increased to 1000 °C at a heating rate of 4 °C / min, then increased to 1380 °C at a heating rate of 2 °C / min, kept at this temperature for 4 h, cooled to 900 °C at a cooling rate of 2 °C / min, then cooled to 600 °C at a cooling rate of 4 °C / min, and finally naturally cooled to room temperature to obtain a sagger.
[0053] Example 3
[0054] A composite quartz sagger comprises the following raw materials in parts by weight: 20 parts of a first fused quartz, 40 parts of a second fused quartz, 5 parts of andalusite, 5 parts of M70 sintered mullite, 16 parts of kaolin, 14 parts of alpha-alumina, 1.5 parts of yellow dextrin, and 2.5 parts of water.
[0055] The particle size of the first fused quartz is 0.1-0.9 mm, and the particle size of the second fused quartz is 1-2 mm.
[0056] The particle size of the M70 sintered mullite is 325 meshes.
[0057] The particle size of the andalusite is 0.1-1 mm.
[0058] The preparation method of the composite quartz sagger comprises the following steps:
[0059] (1) mixing water and yellow dextrin uniformly to obtain a mixture;
[0060] (2) uniformly mixing the first fused quartz and the second fused quartz to obtain mixed fused quartz, and uniformly mixing the mixed fused quartz and the mixture to obtain aggregate;
[0061] (3) mixing the remaining materials uniformly to obtain a base material;
[0062] (4) The aggregate and base material are mixed evenly and aged for 24 h. The aged material is filled into a mold and pressed for 5 min using a 1500 t four-column bidirectional hydraulic press. The pressing pressure is 100 MPa and the ejection pressure is 70 MPa. The temperature is first increased to 480 °C at a heating rate of 2 °C / min, then increased to 1000 °C at a heating rate of 4 °C / min, then increased to 1380 °C at a heating rate of 2 °C / min, kept at this temperature for 4 h, cooled to 900 °C at a cooling rate of 2 °C / min, then cooled to 600 °C at a cooling rate of 4 °C / min, and finally naturally cooled to room temperature to obtain a sagger.
[0063] Example 4
[0064] A composite quartz sagger comprises the following raw materials in parts by weight: 35 parts of first fused quartz, 25 parts of second fused quartz, 10 parts of roller material, 16 parts of kaolin, 14 parts of alpha-alumina, 1.5 parts of yellow dextrin, and 2.5 parts of water.
[0065] The particle size of the first fused quartz is 0.1-0.9 mm, and the particle size of the second fused quartz is 1-2 mm.
[0066] The roller bar stock comprises a first roller bar stock and a second roller bar stock; the particle size of the first roller bar stock is 0.1-1 mm, the particle size of the second roller bar stock is 325 mesh, and the mass ratio of the first roller bar stock to the second roller bar stock is 1:1.
[0067] The preparation method of the composite quartz sagger comprises the following steps:
[0068] (1) mixing water and yellow dextrin uniformly to obtain a mixture;
[0069] (2) uniformly mixing the first fused quartz and the second fused quartz to obtain mixed fused quartz, and uniformly mixing the mixed fused quartz and the mixture to obtain aggregate;
[0070] (3) mixing the remaining materials uniformly to obtain a base material;
[0071] (4) The aggregate and base material are mixed evenly and aged for 24 h. The aged material is filled into a mold and pressed for 5 min using a 1500 t four-column bidirectional hydraulic press. The pressing pressure is 100 MPa and the ejection pressure is 70 MPa. The temperature is first increased to 480 °C at a heating rate of 2 °C / min, then increased to 1000 °C at a heating rate of 4 °C / min, then increased to 1380 °C at a heating rate of 2 °C / min, kept at this temperature for 4 h, cooled to 900 °C at a cooling rate of 2 °C / min, then cooled to 600 °C at a cooling rate of 4 °C / min, and finally naturally cooled to room temperature to obtain a sagger.
[0072] Example 5
[0073] A composite quartz sagger comprises the following raw materials in parts by weight: 30 parts of first fused quartz, 20 parts of second fused quartz, 34 parts of cordierite, 16 parts of kaolin, 2 parts of yellow dextrin, and 2.5 parts of water.
[0074] The particle size of the first fused quartz is 0.1-0.9 mm, and the particle size of the second fused quartz is 1-2 mm.
[0075] The cordierite includes a first cordierite, a second cordierite, and a third cordierite, and the mass ratio of the first cordierite, the second cordierite, and the third cordierite is 5:11:18; the particle size of the first cordierite is 1-2 mm, the particle size of the first cordierite is 1.25-0.2 mesh, and the particle size of the third cordierite is 325 mesh.
[0076] The preparation method of the composite quartz sagger comprises the following steps:
[0077] (1) mixing water and yellow dextrin uniformly to obtain a mixture;
[0078] (2) uniformly mixing the first fused quartz and the second fused quartz to obtain mixed fused quartz, and uniformly mixing the mixed fused quartz and the mixture to obtain aggregate;
[0079] (3) mixing the remaining materials uniformly to obtain a base material;
[0080] (4) The aggregate and base material are mixed evenly and aged for 24 h. The aged material is filled into a mold and pressed for 5 min using a 1500 t four-column bidirectional hydraulic press. The pressing pressure is 100 MPa and the ejection pressure is 70 MPa. The temperature is first increased to 480 °C at a heating rate of 2 °C / min, then increased to 1000 °C at a heating rate of 4 °C / min, then increased to 1380 °C at a heating rate of 2 °C / min, kept at this temperature for 4 h, cooled to 900 °C at a cooling rate of 2 °C / min, then cooled to 600 °C at a cooling rate of 4 °C / min, and finally naturally cooled to room temperature to obtain a sagger.
[0081] Comparative Example 1
[0082] The difference between Comparative Example 1 and Example 1 is that quartz is used in place of fused quartz in Comparative Example 1, and the other aspects are the same.
[0083] A composite quartz sagger comprises the following raw materials in parts by weight: 20 parts of first quartz, 40 parts of second quartz, 10 parts of M70 sintered mullite, 16 parts of kaolin, 14 parts of alpha-alumina, 2 parts of yellow dextrin, and 2.5 parts of water.
[0084] The particle size of the first quartz is 0.1-0.9 mm, and the particle size of the second quartz is 1-2 mm.
[0085] The particle size of the M70 sintered mullite is 325 meshes.
[0086] The preparation method of the composite quartz sagger comprises the following steps:
[0087] (1) mixing water and yellow dextrin uniformly to obtain a mixture;
[0088] (2) mixing the first quartz and the second quartz uniformly to obtain mixed quartz, and mixing the mixed quartz and the mixture uniformly to obtain aggregate;
[0089] (3) mixing the remaining materials uniformly to obtain a base material;
[0090] (4) The aggregate and base material are mixed evenly and aged for 24 h. The aged material is filled into a mold and pressed for 5 min using a 1500 t four-column bidirectional hydraulic press. The pressing pressure is 100 MPa and the ejection pressure is 70 MPa. The temperature is first increased to 480 °C at a heating rate of 2 °C / min, then increased to 1000 °C at a heating rate of 4 °C / min, then increased to 1380 °C at a heating rate of 2 °C / min, kept at this temperature for 4 h, cooled to 900 °C at a cooling rate of 2 °C / min, then cooled to 600 °C at a cooling rate of 4 °C / min, and finally naturally cooled to room temperature to obtain a sagger.
[0091] Comparative Example 2
[0092] A composite quartz sagger comprises the following raw materials in parts by weight: 60 parts of first fused quartz, 10 parts of M70 sintered mullite, 16 parts of kaolin, 14 parts of alpha-alumina, 2 parts of yellow dextrin, and 2.5 parts of water.
[0093] The particle size of the first fused quartz is 0.1-0.9 mm.
[0094] The particle size of the M70 sintered mullite is 325 meshes.
[0095] The preparation method of the composite quartz sagger comprises the following steps:
[0096] (1) mixing water and yellow dextrin uniformly to obtain a mixture;
[0097] (2) uniformly mixing the first fused quartz with the mixture to obtain aggregate;
[0098] (3) mixing the remaining materials uniformly to obtain a base material;
[0099] (4) The aggregate and base material are mixed evenly and aged for 24 h. The aged material is filled into a mold and pressed for 5 min using a 1500 t four-column bidirectional hydraulic press. The pressing pressure is 100 MPa and the ejection pressure is 70 MPa. The temperature is first increased to 480 °C at a heating rate of 2 °C / min, then increased to 1000 °C at a heating rate of 4 °C / min, then increased to 1380 °C at a heating rate of 2 °C / min, kept at this temperature for 4 h, cooled to 900 °C at a cooling rate of 2 °C / min, then cooled to 600 °C at a cooling rate of 4 °C / min, and finally naturally cooled to room temperature to obtain a sagger.
[0100] Comparative Example 3
[0101] A composite quartz sagger comprises the following raw materials in parts by weight: 60 parts of second fused quartz, 10 parts of M70 sintered mullite, 16 parts of kaolin, 14 parts of alpha-alumina, 2 parts of yellow dextrin, and 2.5 parts of water.
[0102] The particle size of the second fused quartz is 1 to 2 mm.
[0103] The particle size of the M70 sintered mullite is 325 meshes.
[0104] The preparation method of the composite quartz sagger comprises the following steps:
[0105] (1) mixing water and yellow dextrin uniformly to obtain a mixture;
[0106] (2) uniformly mixing the second fused quartz with the mixture to obtain aggregate;
[0107] (3) mixing the remaining materials uniformly to obtain a base material;
[0108] (4) The aggregate and base material are mixed evenly and aged for 24 h. The aged material is filled into a mold and pressed for 5 min using a 1500 t four-column bidirectional hydraulic press. The pressing pressure is 100 MPa and the ejection pressure is 70 MPa. The temperature is first increased to 480 °C at a heating rate of 2 °C / min, then increased to 1000 °C at a heating rate of 4 °C / min, then increased to 1380 °C at a heating rate of 2 °C / min, kept at this temperature for 4 h, cooled to 900 °C at a cooling rate of 2 °C / min, then cooled to 600 °C at a cooling rate of 4 °C / min, and finally naturally cooled to room temperature to obtain a sagger.
[0109] Comparative Example 4
[0110] A composite quartz sagger comprises the following raw materials in parts by weight: 10 parts of first fused quartz, 20 parts of second fused quartz, 20 parts of M70 sintered mullite, 26 parts of kaolin, 24 parts of alpha-alumina, 2 parts of yellow dextrin, and 2.5 parts of water.
[0111] The particle size of the first fused quartz is 0.1-0.9 mm, and the particle size of the second fused quartz is 1-2 mm.
[0112] The particle size of the M70 sintered mullite is 325 meshes.
[0113] The preparation method of the composite quartz sagger comprises the following steps:
[0114] (1) mixing water and yellow dextrin uniformly to obtain a mixture;
[0115] (2) uniformly mixing the first fused quartz and the second fused quartz to obtain mixed fused quartz, and uniformly mixing the mixed fused quartz and the mixture to obtain aggregate;
[0116] (3) mixing the remaining materials uniformly to obtain a base material;
[0117] (4) The aggregate and base material are mixed evenly and aged for 24 h. The aged material is filled into a mold and pressed for 5 min using a 1500 t four-column bidirectional hydraulic press. The pressing pressure is 100 MPa and the ejection pressure is 70 MPa. The temperature is first increased to 480 °C at a heating rate of 2 °C / min, then increased to 1000 °C at a heating rate of 4 °C / min, then increased to 1380 °C at a heating rate of 2 °C / min, kept at this temperature for 4 h, cooled to 900 °C at a cooling rate of 2 °C / min, then cooled to 600 °C at a cooling rate of 4 °C / min, and finally naturally cooled to room temperature to obtain a sagger.
[0118] Comparative Example 5
[0119] A composite quartz sagger comprises the following raw materials in parts by weight: 20 parts of first fused quartz, 40 parts of second fused quartz, 10 parts of M70 sintered mullite, 16 parts of kaolin, 14 parts of alpha-alumina, 2 parts of yellow dextrin, and 2.5 parts of water.
[0120] The particle size of the first fused quartz is 0.1-0.9 mm, and the particle size of the second fused quartz is 1-2 mm.
[0121] The particle size of the M70 sintered mullite is 325 meshes.
[0122] The preparation method of the composite quartz sagger comprises the following steps:
[0123] (1) mixing water and yellow dextrin uniformly to obtain a mixture;
[0124] (2) uniformly mixing the first fused quartz and the second fused quartz to obtain mixed fused quartz, and uniformly mixing the mixed fused quartz and the mixture to obtain aggregate;
[0125] (3) mixing the remaining materials uniformly to obtain a base material;
[0126] (4) The aggregate and base material are mixed evenly and aged for 24 h. The aged material is filled into a mold and pressed for 5 min using a 1500-ton four-column bidirectional hydraulic press. The pressing pressure is 100 MPa and the ejection pressure is 70 MPa. The temperature is increased to 1380 °C at a heating rate of 2 °C / min, kept at this temperature for 4 h, and naturally cooled to room temperature to obtain a sagger.
[0127] Comparative Example 6
[0128] A composite quartz sagger comprises the following raw materials in parts by weight: 20 parts of first fused quartz, 40 parts of second fused quartz, 10 parts of M70 sintered mullite, 16 parts of kaolin, 14 parts of alpha-alumina, 2 parts of yellow dextrin, and 2.5 parts of water.
[0129] The particle size of the first fused quartz is 0.1-0.9 mm, and the particle size of the second fused quartz is 1-2 mm.
[0130] The particle size of the M70 sintered mullite is 325 meshes.
[0131] The preparation method of the composite quartz sagger comprises the following steps:
[0132] (1) mixing water and yellow dextrin uniformly to obtain a mixture;
[0133] (2) uniformly mixing the first fused quartz and the second fused quartz to obtain mixed fused quartz, and uniformly mixing the mixed fused quartz and the mixture to obtain aggregate;
[0134] (3) mixing the remaining materials uniformly to obtain a base material;
[0135] (4) The aggregate and base material are mixed evenly and aged for 24 h. The aged material is filled into a mold and pressed for 5 min using a 1500 t four-column bidirectional hydraulic press. The pressing pressure is 100 MPa and the ejection pressure is 70 MPa. The temperature is first increased to 480 °C at a heating rate of 5 °C / min, then increased to 1000 °C at a heating rate of 5 °C / min, then increased to 1380 °C at a heating rate of 5 °C / min, kept at this temperature for 4 h, cooled to 900 °C at a cooling rate of 5 °C / min, then cooled to 600 °C at a cooling rate of 5 °C / min, and finally naturally cooled to room temperature to obtain a sagger.
[0136] Test Case
[0137] Among them, the performance of the composite quartz sagger is shown in Table 1.
[0138] The water-cooled thermal shock test process is as follows: Figure 1 shown.
[0139] Table 1
[0140]
[0141] As can be seen from Table 1, the composite quartz sagger described in the present invention has the characteristics of small thermal expansion coefficient, high dimensional accuracy of finished products, no deformation at high temperature, good water-cooled thermal shock stability, good chemical corrosion resistance, etc., and can be applied to various non-alkaline environments and high-temperature calcination environments with rapid temperature rise and fall.
[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A composite quartz sagger, characterized in that: The thermal expansion coefficient of the sagger is ≤2.0×10 -6 / ℃, the sagger does not crack when water-cooled at a temperature of 1100℃, and the use temperature of the sagger is ≤1300℃; The sagger uses first fused quartz and second fused quartz as aggregates; the particle size of the first fused quartz is 0.1-0.9 mm, and the particle size of the second fused quartz is 1-2 mm; the first fused quartz accounts for 18-40% of the raw materials for preparing the sagger; the second fused quartz accounts for 18-40% of the raw materials for preparing the sagger.
2. The composite quartz sagger according to claim 1, characterized in that: The sagger comprises the following raw materials in parts by weight: 20 to 40 parts of first fused quartz, 20 to 40 parts of second fused quartz, 0 to 20 parts of roller stock, 0 to 20 parts of M70 sintered mullite, 10 to 20 parts of kaolin, 0 to 20 parts of α-alumina, 0 to 40 parts of cordierite, 0 to 20 parts of andalusite, 1 to 5 parts of a binder, and 1 to 5 parts of water.
3. The composite quartz sagger according to claim 1, characterized in that: The sagger comprises the following raw materials in parts by weight: 20-40 parts of first fused quartz, 20-40 parts of second fused quartz, 5-10 parts of M70 sintered mullite, 15-18 parts of kaolin, 13-15 parts of α-alumina, 0-5 parts of andalusite, 1.5-2 parts of binder, and 2-3 parts of water.
4. The composite quartz sagger according to claim 2, characterized in that: The particle size of the M70 sintered mullite is 300-350 meshes.
5. The composite quartz sagger according to claim 2, characterized in that: The particle size of the andalusite is 0.1-1 mm.
6. The composite quartz sagger according to claim 2, characterized in that: The binder is at least one of sodium lignin sulfonate, calcium lignin sulfonate, peach gum, yellow dextrin, white dextrin, polyvinyl alcohol, polyethylene glycol, 801 glue powder, carboxymethyl cellulose, and hydroxypropyl methyl cellulose.
7. The method for preparing a composite quartz sagger according to any one of claims 2 to 6, characterized in that: The following steps are involved: (1) mixing water and a binder uniformly to obtain a mixture; (2) uniformly mixing the first fused quartz and the second fused quartz to obtain mixed fused quartz, and uniformly mixing the mixed fused quartz and the mixture to obtain aggregate; (3) mixing the remaining materials uniformly to obtain a base material; (4) The aggregate and base material are mixed evenly, aged, filled into a mold, pressed, and sintered to obtain a sagger.
8. The composite quartz sagger according to claim 7, characterized in that: The pressing adopts a four-column bidirectional hydraulic press, the pressing pressure is 90-120 MPa, the ejection pressure is 60-80 MPa, and the pressing time is 2-10 minutes.
9. The composite quartz sagger according to claim 7, characterized in that: The sintering is specifically as follows: firstly, the temperature is increased to 450-500°C at a heating rate of 1-3°C / min, then the temperature is increased to 950-1000°C at a heating rate of 3-5°C / min, then the temperature is increased to 1320-1400°C at a heating rate of 1-3°C / min, and the temperature is kept at 3-5h, then the temperature is decreased to 900-950°C at a cooling rate of 1-3°C / min, then the temperature is decreased to 550-600°C at a cooling rate of 3-5°C / min, and finally the temperature is naturally cooled to room temperature.
10. Use of the composite quartz sagger according to any one of claims 1 to 6 in preparing positive electrode materials.
Citation Information
Patent Citations
Sagger
CN105669223A
Preparation method of clay quartz crucible for high-temperature alloy casting
CN111333425A
Preparation process of fused quartz with high fire resistance
CN112250431A
Method for prodn. of quartz cordierite kiln ware
CN1126186A
Method for preparing material with high thermal expansion coefficient through microwave heating by using industrial wastes
CN112939588A
